Doping effect of carboxylic acids on optical, electrical, mechanical and thermal traits of KDP crystal. (10th November 2017) - Anis, Mohd; Muley, G. G.; Baig, M. I.; Hussaini, S. S.; Shirsat, M. D.
Abstract: Single crystals of maleic acid (MA)- and oxalic acid (OA)-doped potassium dihydrogen phosphate (KDP) materials have been grown by slow evaporation solution technique. The structural parameters of the grown crystals have been determined using the single crystal X-ray diffraction technique. Fourier transform infrared analysis has been done to identify the functional groups of grown crystals. The modifications in optical transmittance, optical band gap and different optical constants of KDP crystal due to addition of MA and OA have been investigated by means of UV–Visible spectral analysis. The Vicker's microhardness studies have been carried out to examine the mechanical behaviour of pure and doped KDP crystals. The influence of dopants on thermal stability of KDP crystal has been investigated using the thermogravimetric and differential thermal analysis. The dielectric constant, dielectric loss, ac resistivity and ac conductivity of pure and doped KDP crystals were evaluated under dielectric studies.